The Massali Tradition in Bugis Society: Ritual Meaning, Cultural Health Beliefs, and Social Change in Bompo, Bone Regency - Ruhushandy, Ichwan Erlangga; Bahri, Bahri; Ahmadin, Ahmadin; Najamuddin, Najamuddin (Jurnal Sosiologi Agama Indonesia (JSAI), 2026)
This study examines the Massali tradition in the Bugis community of Bompo Hamlet, Mattampa Bulu Village, Lamuru District, Bone Regency, Indonesia. Massali is a collective fasting tradition based on the restriction of animal-based foods and other customary prohibitions that continue to shape community life. The study aims to analyze the socio-cultural background of the tradition, explore the meanings attributed to the practice by community members, and examine the dynamics of its contemporary transformation. This research employed a qualitative design grounded in a sociological approach. Data were collected through in-depth interviews, field observations, and documentation involving fifteen informants, including customary leaders, religious figures, community leaders, health workers, and community members. The data were analyzed thematically through processes of data reduction, data display, and conclusion drawing, supported by source and method triangulation. The findings show that Massali originates from a long-standing customary tradition associated with ancestral authority and oral transmission within Bugis society. The tradition is understood by community members as a form of ritual discipline that expresses self-control, social responsibility, and bodily balance. It also reflects a locally grounded system of cultural health beliefs, especially through food restrictions, behavioral discipline, and ritual purification. The study further shows that Massali has undergone gradual reinterpretation in response to changing social and religious contexts, particularly through the incorporation of Islamic elements into the ritual process. These findings indicate that Massali continues to function as a cultural institution that connects ancestral heritage, social regulation, and contemporary religious life in the Bugis community of Bompo.